ABOUT THE COMPLEXITY AND MORTALITY AMONG PATIENTS WITH PANCREATIC NECROSIS - Khamdamov, B.Z.; Musoev, T.Y.; Khaydarov, F.N.; Ganiyev, A.A.; Boboev, K.Kh.; Abdurakhmanov, F.M.; Korikhonov, D.N.; Khamdamov, Sh.A.; Bobokulova, Sh.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Diagnostics and surgical tactics for pancreatic necrosis remain in our time in the aggregate one of the far-from solved problems in urgent abdominal surgery. There is no doubt that this problem is related to the difficulties of predicting and early diagnosis of destructive forms of acute pancreatitis. Material. A retrospective cohort study of the results of a comprehensive examination and treatment of 97 patients with pancreatic necrosis was conducted. All patients were treated and examined in the Bukhara regional branch of the Republican Scientific and Practical Medical Center for Emergency Medical Care from 2013 to 2017. Conclusion. The high mortality rate among patients who have undergone repeated relaparotomy indicates that it is necessary to delay their implementation in infected pancreatic necrosis. They are acceptable when they are performed in conditions of delimitation of processes. Delimited necrosis of the pancreas is lysed and sequestered. In such cases, the sanitizing and draining goal of surgery is easily achievable. This is what allows you to perform the surgical intervention in a more than favourable background, as it will be less traumatic.